A Cultural-Historical Activity Theory Perspective on the Sustainability Challenges of Urban Commoning: Revisiting the Material Aspect of the (Re)Production of Urban Commons - Popović, Isidora (International Review of Theoretical Psychologies, 2026)
Urban commoning theory gives priority to value that is reproduced in the patterns of collective use of urban resources. Its theoretical aim is to reclaim this value from capital, as a commons. Urban commoning is often recognized as an alternative to capitalist reproduction in the fields of art, culture, or housing - such as in autonomous cultural centers or housing cooperatives. However, one of the key empirical issues of urban commoning is its relative unsustainability. This typically manifests in the low participation of commoners in the everyday activities of commoning. The aim of this paper was to show that commoning theory lacks the analytical tools necessary to account for these challenges and to propose a pathway to a theoretical solution. A critical re-examination of some aspects of urban commoning theory is presented, in order to better understand its shortcomings. The argument takes into account the theoretical function of an established critique of Hardin and Ostrom in the setting of the grounds for commoning theory, as well as a particular historization of commoning that contextualizes it. I argue that these established ways of contextualizing commoning theory serve to obscure its relationship to public interest, as well as to remove the notion of economic interest from commoning. Instead of a widely spread focus on values and personal emancipation, central to commoning theory, a more structural approach to commoning is proposed. Based on Silvia Federici’s notions of wages against housework and the Cultural-historical activity theory, commoning is discussed as a contradictory activity. I propose the notion of urban commoning as unpaid reproductive work that has an implicit opportunity cost for the commoners.